SEPARATION AND DETERMINATION OF THE R-ISOMER OF KETOPROFEN IN A BULK DRUG SUBSTANCE BY NORMAL PHASE LIQUID CHROMATOGRAPHY - Lawande, Appasaheb B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective is defined to develop and validate simple, rapid, precise, and accurate for separation and determination of R-isomer impurity of ketoprofen bulk drug material by the normal phase high-performance liquid chromatographic method as per the International Conference of Harmonization Guideline (ICH) guidelines. Methods: The R-isomer and S-isomer were baseline resolved on a Chiralcel OJ-H, 150 mm × 4.6 mm, and 5 µm stationary phase column. Mobile phase system containing n-hexane:isopropyl alcohol:glacial acetic acid (50:50:0.1 v/v.). The detector wavelength has been selected 254 nm and column oven temperature 25°C. The chromatographic resolutions between R-isomer and S-isomer were more than two. The developed method was extensively validated according to ICH guidelines. Results: Ketoprofen linearity was found for R-isomer over the concentration range of 600-6000 ng/ml, with the linear regression (Correlation coefficient R=0.999) and proved to be robust. The limit of detection and limit of quantification of ketoprofen R-isomer were found to be 200 and600 ng/ml. The percentage recovery of R-isomer has been ranged from 97.5 to 102.0 in bulk drug material samples of ketoprofen. The proposed method was found to be suitable and accurate for the quantitative determination of R-isomer of ketoprofen in bulk drug sample. Conclusion: A simple, rapid, precise, and accurate normal phase liquid chromatography method has been developed and validated to determineR-isomer impurity of ketoprofen in bulk drugs material as per ICH. Keywords: Ketoprofen, High-performance liquid chromatography, Known impurity, Normal phase, Chiralcel OJ-H, Validation.